2018
DOI: 10.1038/s41589-018-0038-z
|View full text |Cite
|
Sign up to set email alerts
|

The cyanobacterial ornithine–ammonia cycle involves an arginine dihydrolase

Abstract: Living organisms have evolved mechanisms for adjusting their metabolism to adapt to environmental nutrient availability. Terrestrial animals utilize the ornithine-urea cycle to dispose of excess nitrogen derived from dietary protein. Here, we identified an active ornithine-ammonia cycle (OAC) in cyanobacteria through an approach combining dynamic N andC tracers, metabolomics, and mathematical modeling. The pathway starts with carbamoyl phosphate synthesis by the bacterial- and plant-type glutamine-dependent en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
94
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 50 publications
5
94
0
Order By: Relevance
“…Furthermore, ornithine was found to peculiarly serve as the substrate for MAAs synthesis in N. flagelliforme CCNUN1 (Shang et al, ). Recently, an active ornithine–ammonia cycle was identified in cyanobacteria with the conversion of arginine to ornithine and ammonia by a novel arginine dihydrolase, ArgZ (Zhang et al, ). This gives convincing evidence for the MAAs biosynthetic pathway in N. flagelliforme CCNUN1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, ornithine was found to peculiarly serve as the substrate for MAAs synthesis in N. flagelliforme CCNUN1 (Shang et al, ). Recently, an active ornithine–ammonia cycle was identified in cyanobacteria with the conversion of arginine to ornithine and ammonia by a novel arginine dihydrolase, ArgZ (Zhang et al, ). This gives convincing evidence for the MAAs biosynthetic pathway in N. flagelliforme CCNUN1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Schematic representation of the changes in expression of genes involved in carbon metabolism and nitrogen assimilation and incorporation based on the KEGG database and referred to Zhang et al, . Genes encoding metabolic enzymes are available in Supporting Information Table S12.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same conclusion has been recently reported for a homologous protein from the unicellular cyanobacterium Synechocystis sp. PCC 6803 (Zhang et al , ). No production of proline from ornithine was, however, observed with the whole His‐tagged AgrE protein assayed under different incubation conditions.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study identified an arginine dihydrolase encoded by gene argZ (designated as agrE by Burnat, Picossi et al, 2019), which catalyzes the conversion of arginine into ornithine and ammonia ( Fig. 1) (Zhang et al, 2018). This enzyme has been identified as the major arginine-degrading enzyme in a model cyanobacterium Synechocystis sp.…”
mentioning
confidence: 99%